Peningkatan Hasil Belajar Penyajian Data Menggunakan Model Project Based Learning di Sekolah Dasar - Faradilla, Amelia; Zuryanty, Zuryanty (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
Mathematics learning outcomes in elementary school are very low, to overcome these problems an effective approach is needed. This study aims to improve mathematics learning outcomes using the project based learning (PjBl) model on data presentation material in class IV of SDN 30 Cengkeh, Padang City. This research is a classroom action research (CAR) that uses a qualitative and quantitative approach. Conducted in two cycles, with two meetings covering four stages, namely planning, implementation, observation, and reflection. The subjects of this study were teachers and fourth grade students of 30 Cengkeh Elementary School in Padang City, amounting to 28 people. The results showed that there was an increase in the average mathematics learning outcomes of students in the first cycle of 62.75 to 91.07 in the second cycle using the project based learning (PjBl) model.